A specialization of definitions in common knowledge logic - Girčys, Aurimas Paulius; Pliuškevičius, Regimantas (Lietuvos matematikos rinkinys, 2011)
It is known that one of main aims of specializations of derivations in nonclassical logics is the various tools which allow us to simplify the searching of termination of derivations. The traditional techniques used to ensure termination of derivations in various non-classical logics are based on loop-checking. In this paper the reflexive common knowledge logic based on modal logic K2 is considered. For considered logic a sequent calculus with specialized non-logical (loop-type) axioms is presented.